Expression of the semicarbazide-sensitive amine oxidase in articular cartilage: its role in terminal differentiation of chondrocytes in rat and human. Issue 7 (July 2016) - Filip, A.; Pinzano, A.; Bianchi, A.; Fève, B.; Jalkanen, S.; Gillet, P.; Mainard, D.; Lacolley, P.; Magdalou, J.; Mercier, N.
Summary: Objective: Semicarbazide-sensitive amine oxidase (SSAO) catalyzes the oxidation of primary amines into ammonia and reactive species (hydrogen peroxide, aldehydes). It is highly expressed in mammalian tissues, especially in vascular smooth muscle cells and adipocytes, where it plays a role in cell differentiation and glucose transport. The study aims at characterizing the expression and the activity of SSAO in rat and human articular cartilage of the knee, and to investigate its potential role in chondrocyte terminal differentiation. Design: SSAO expression was examined by immunohistochemistry and western blot. Enzyme activity was measured using radiolabeled benzylamine as a substrate. Primary cell cultures of rat chondrocytes were treated for 21 days by a specific SSAO inhibitor, LJP 1586. Terminal chondrocyte differentiation markers were quantified by RT-qPCR. The basal and IL1β-stimulated glucose transport was monitored by the entrance of 3 [H]2-deoxyglucose in chondrocytes. Results: SSAO was expressed in chondrocytes of rat and human articular cartilage. SSAO expression was significantly enhanced during the hypertrophic differentiation of chondrocytes characterized by an increase in MMP13 and in alkaline phosphatase (ALP) expressions. SSAO inhibition delayed the late stage of chondrocyte differentiation without cell survival alteration and diminished the basal and IL1β-stimulated glucose transport. Interestingly, SSAO activity was strongly increased in human osteoarthritic cartilage. Conclusions: SSAO was expressed as an active form in rat and human cartilage. The results suggest the involvement of SSAO in rat chondrocyte terminal differentiation via a modulation of the glucose transport. In man, the increased SSAO activity detected in osteoarthritic patients may trigger hypertrophy and cartilage degeneration.